Model zaposlenosti: možna rešitev problema brezposelnosti? - Lorenčič, Eva (Naše gospodarstvo, 2013)
Unemployment inflicts costs on the government budget, on the unemployed individual, and on the society as a whole in many ways. The paper summarizes the findings of published research on negative consequences of unemployment and as such founds the need to solve the problem of unemployment. It discusses the Model of Employment, which is a possible solution to the problem of unemployment and thus addresses the need to reduce the costs of unemployment. The crux of the model is a redistribution of the total number ofworkplaces and total annual working hours among the "new actively employed population". The model takes into account the fact that there should be a match between the requirements of a workplace and the educational profile of a prospective employee.
Keywords: brezposelnost; unemployment; stroški; zaposlovanje; modeli